2020
DOI: 10.1002/14651858.cd012740.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ab interno trabecular bypass surgery with Schlemm´s canal microstent (Hydrus) for open angle glaucoma

Abstract: Ab interno trabecular bypass surgery with Schlemm´s Canal Microstent (Hydrus) for open angle glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…Accordingly, stent implantation through MIGS should be an effective method of treating POAG, as its IOP-lowering effect is based on bypassing this crucial site of AH outflow resistance. This is supported by the above mentioned studies: IOP is reduced on average by 10-26% by the iStent Ò (Spiegel et al 2009;Seiboldet al 2016), up to 40% by the Hydrus Ò (Otarola et al 2020), and 29-42% with the Xen Ò (De Gregorio et al 2018); the PRESERFLO Ò Micro-Shunt is even better, averaging 30-55%. These studies differ widely in reported results and evidence.…”
Section: Discussionmentioning
confidence: 61%
“…Accordingly, stent implantation through MIGS should be an effective method of treating POAG, as its IOP-lowering effect is based on bypassing this crucial site of AH outflow resistance. This is supported by the above mentioned studies: IOP is reduced on average by 10-26% by the iStent Ò (Spiegel et al 2009;Seiboldet al 2016), up to 40% by the Hydrus Ò (Otarola et al 2020), and 29-42% with the Xen Ò (De Gregorio et al 2018); the PRESERFLO Ò Micro-Shunt is even better, averaging 30-55%. These studies differ widely in reported results and evidence.…”
Section: Discussionmentioning
confidence: 61%
“…A 2020 Cochrane Systematic Review found moderate evidence that the Hydrus microstent in the short term is more effective when compared to iStent for lowering IOP in patients with OAG. 604 (I, Moderate Quality, Strong Recommendation)…”
Section: P109mentioning
confidence: 99%
“…At 1 year, more HMS had complete success (p < 0.001) and more were medication-free (difference = 22.6%, p = 0.0057). 168,169 Compared to ab externo canaloplasty, HMS performed similarly over 2 years. 170 The most common adverse finding was nonobstructive (14.9%) and obstructive (3.8%) PAS.…”
Section: Hydrus Microstentmentioning
confidence: 99%